Pemanfaatan Aplikasi Buku Tamu Berbasis Digital Pada Desa Arang Limbung Kabupaten Kuburaya - Riski Annisa; Sri Murni; Panny Agustia Rahayuningsih; Raja Sabarudin (Yayasan Literasi Sains Indonesia, 2022)
The progress of the development of computing and telecommunications has changed the way of life in the world in carrying out everyday activities. Desa Arang Limbung is the center of Government of Kubu Raya. In carrying out the duties of the government of development and society, the village head always coordinated with the community and other village institutions. To set the Village Head Meeting Schedule, a Guest Book Application The Role of the Guest Book is always limited to the administration, so it cannot be used as a benchmark to measure the level of village office services, because to use it further, the existing data must be summarized to produce information needed. The community service team conducts training using a digital guest book application that can be used to measure the number of visits at the village office while providing information about anyone in the village office which will be encountered by guests who come to the village office.